Aspetos dos demonstrativos em português europeu: deixis e anáfora - Fragoso, Andreia (elingUP: Revista Eletrónica de Linguística dos Estudantes da Universidade do Porto, 2018)
This research paper focus on the analysis of anaphoric chains in constructions with the demonstratives este/esse/aquele, and it was developed within the unit course of Projeto, which is included in the Language Sciences undergraduate degree. For the data collection, two written corpora (CETEMPúblico and Corpus de Referência do Português Contemporâneo) were used. The main objectives of this work are to verify the difference of meaning between este and esse, to analyze the anaphoric contexts in which it appears aquele, to observe to what extent verbal tenses influences the demonstrative use and, finally, to make a brief presentation of the definite article and to understand in what form it establishes a relation with the demonstratives.